New wasps of †Falsiformicidae from mid-Cretaceous Kachin amber - Zhen Wang; Alexandr P. Rasnitsyn; Evgeny E. Perkovsky; Lars Vilhelmsen; Taiping Gao (Journal of Hymenoptera Research)
Two new species of the family †Falsiformicidae Rasnitsyn, 1975, Siccibythus robustus sp. nov. and Siccibythus aristovi sp. nov., are described from the mid-Cretaceous Kachin amber based on three well-preserved specimens. The new species belongs to †Siccibythus Cockx & McKellar, 2016, based on the elongate pronotum and fore wing with cells 2+3rm and 3r not enclosed with tubular veins. We summarize the diversity and distribution for all species of †Falsiformicidae and provide a revised key to the family. These new findings enhance the diversity of †Falsiformicidae in Kachin amber.